2016
DOI: 10.1177/1756283x16652325
|View full text |Cite
|
Sign up to set email alerts
|

Closure of gastrointestinal defects with Ovesco clip: long-term results and clinical implications

Abstract: Background:The Over-The-Scope Clip (OTSC®, Ovesco Endoscopy GmbH, Tübingen, Germany) is an innovative clipping device that provides a strong tissue grasp and compression without provoking ischemia or laceration. In this retrospective study we evaluated immediate and long-term success rates of OTSC deployment in various pathologies of the gastrointestinal (GI) tract.Methods:A total of 45 patients (35 female, 10 male) with an average age of 56 years old (range, 24–90 years) were treated with an OTSC for GI defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…Among them, PubMed searches including studies with 10 or more cases of describing experience with the OTSC system, using “Over‐The‐Scope Clip” and “endoscopic closure” as key terms, lead to 30 literature references. The clinical results are summarized in Table …”
Section: Overall Clinical Outcomes Of the Over‐the‐scope Clip Systemmentioning
confidence: 99%
“…Among them, PubMed searches including studies with 10 or more cases of describing experience with the OTSC system, using “Over‐The‐Scope Clip” and “endoscopic closure” as key terms, lead to 30 literature references. The clinical results are summarized in Table …”
Section: Overall Clinical Outcomes Of the Over‐the‐scope Clip Systemmentioning
confidence: 99%
“…OTSCs differ from traditional through-the-scope clips in several characteristics, namely higher compression force, larger diameter and grasping accessories that allow the closure of wall defects of up to 30 mm, including the muscle layer[ 42 - 44 ]. They have been successfully used and validated in literature in different settings, i.e ., haemostasis in acute GI bleeding, closure of GI perforations, leaks and fistulas or as anchor to prevent stent migration[ 45 ]. While clinical success is nearly 100% for haemostasis, it decreases to 40%-75% for GI defect closure, with best outcomes in acute perforations, which have fresh edges with less fibrosis[ 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A long indwelling time of OTS reflects its correct deployment over a suitable tissue and translates into a higher long-term clinical success. Donatelli et al[ 17 ] reported OTS clip outcome in a retrospective study comprising 45 patients, who presented both iatrogenic acute perforation (15 pts) as well as post-surgical leak and fistula (30 pts). In the latter group OTS clips were used as a rescue therapy after previous endoscopic treatments.…”
Section: Endoclipsmentioning
confidence: 99%